Women in love - Lawrence, D. H. 1885-1930; Delerue, Georges 1925-1992 (The Criterion Collection, 2018)
"Die Geschichte zweier Schwestern, die an zwei einander in bedingungsloser Freundschaft ergebene Männer geraten, woran schließlich das Glück der einen scheitert. Die in den 20er Jahren spielende Handlung läßt ideologische und psychologische Strömungen erkennen, die auch heute noch aktuell sind ... [...]" [filmdienst.de]
Original: Großbritannien 1969
Two-DVD special edition features: new, restored 4K digital transfer ; two 2003 commentaries featuring director Ken Russell and screenwriter and producer Larry Kramer ; segments from a 2007 interview with Russell for the BAFTA Los Angeles Heritage Archive ; A British picture: Portrait of an enfant terrible, Russell’s 1989 biopic on his own life and career ; interview from 1976 with actor Glenda Jackson ; interviews with Kramer and actors Alan Bates and Jennie Linden from the set ; new interviews with director of photography Billy Williams and editor Michael Bradsell ; Second best, a 1972 short film based on a D. H. Lawrence story, produced by and starring Bates ; trailer ; plus: An essay by scholar Linda Ruth Williams
Bildformat 1.75:1
Keywords: Film; DVD-Video